2005
DOI: 10.1093/carcin/bgi089
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of aberrant crypt foci and apoptosis by dietary herbal supplements (quercetin, curcumin, silymarin, ginseng and rutin)

Abstract: It is estimated that one-third of Americans use dietary herbal supplements on a regular basis. Diets rich in bioactive phytochemicals are associated with reduced risk of certain cancers, notably, colon cancer. Herbal supplements have not been directly tested as sources of bioactive cancer preventives. Hence, this study compares the ability of four herbal flavonoids (quercetin, curcumin, rutin and silymarin) and one whole herb mixture (ginseng powder) to suppress aberrant crypt foci (ACF) in an azoxymethane (AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
130
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(142 citation statements)
references
References 21 publications
8
130
0
4
Order By: Relevance
“…In addition, it is possible that these anticancer effects were due to the synergistic action of chlorogenic acid with other compounds such as ursolic acid and rutin [3,4], also present in YMT. It has been reported that ursolic induced apoptosis on HT-29 cells by suppressing EGFR/MAPK pathway [22], and rutin decreased by 1.2-fold the number of aberrant crypt foci in an azoxymethane-induced CRC in rats [23].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, it is possible that these anticancer effects were due to the synergistic action of chlorogenic acid with other compounds such as ursolic acid and rutin [3,4], also present in YMT. It has been reported that ursolic induced apoptosis on HT-29 cells by suppressing EGFR/MAPK pathway [22], and rutin decreased by 1.2-fold the number of aberrant crypt foci in an azoxymethane-induced CRC in rats [23].…”
Section: Discussionmentioning
confidence: 95%
“…In the first study, authors report that rats fed with silymarin supplemented diet led to significant decrease in number of aberrant crypt foci (represent precursor lesions for colonic adenomas) in an azoxymethane (AOM)-induced rat colon cancer model (Volate et al, 2005). In another similar but more detailed study, it was observed that silymarin administration through diet for 4 weeks either during or after carcinogen (Azoxymethane) exposure led to a significant reduction in the frequency of aberrant crypt foci formation.…”
Section: Colon Cancermentioning
confidence: 99%
“…In vivo studies have been performed to depict the chemopreventive properties of quercetin on different cancers. Volate et al [188] found that food supplementation of approximately 3% quercetin exerts significantly beneficial effects by decreasing precancerous lesions through induction of cellular. Dihal et al [189] reported that quercetin inhibits azoxymethane-induced colorectal carcinogenesis in F344 rats.…”
Section: Quercetinmentioning
confidence: 99%